2003
DOI: 10.1007/s00213-002-1358-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and motor function after administration of hydrocodone bitartrate plus ibuprofen, ibuprofen alone, or placebo in healthy subjects with exercise-induced muscle damage: a randomized, repeated-dose, placebo-controlled study

Abstract: Hydrocodone plus ibuprofen was not associated with deterioration in complex cognition but was related to very transitory decrements in tasks involving simple hand-eye coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…There was an insufficient number of participants taking opioids in our study sample to examine this relationship. Others have shown that patients taking opioids may suffer decline in cognitive function [75], but there is substantial interindividual and inter‐opioid variability in this phenomenon [19,76,77]. Our study results combined with that of others should prompt practitioners to prescribe opioids for patients with chronic nonmalignant pain carefully and methodically.…”
Section: Discussionsupporting
confidence: 56%
“…There was an insufficient number of participants taking opioids in our study sample to examine this relationship. Others have shown that patients taking opioids may suffer decline in cognitive function [75], but there is substantial interindividual and inter‐opioid variability in this phenomenon [19,76,77]. Our study results combined with that of others should prompt practitioners to prescribe opioids for patients with chronic nonmalignant pain carefully and methodically.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, the negative effects of other antiinflammatory analgesic drugs should be considered. For instance, based on a double-blind, randomized, placebo-controlled, repeated-dose clinical trial, patients taking hydrocodone bitartrate plus ibuprofen performed significantly worse on simple tracking task and reactiontime task [53]. Additionally, cautions should be taken when prescribing drugs that could affect the cerebral blood supply as side effects as it can affect the oxygen supply and other nutrients to the brain [52].…”
Section: Possible Explanations Of the Underlying Mechanismsmentioning
confidence: 99%
“…And at least one study reported that increased caffeine consumption is linked with increased risk-taking in adolescents ( Temple et al, 2017b ). Finally, prescription stimulant medications have been linked with cognitive enhancement ( Bagot and Kaminer, 2014 ; Coghill et al, 2014 ; Tamminga et al, 2016 ), while prescription anxiolytics/sedatives ( Meador et al, 2011 ; Loring et al, 2012 ; Reissig et al, 2015 ; Ghoneim et al, 1984 ) and opiates ( Allen et al, 2003 ; Schoedel et al, 2010 ) negatively impact memory, processing speed and attention. Over the counter (OTC) cough medication containing dextromethorphan has been linked with cortical thickness in adolescents in one study ( Qiu et al, 2016 ), although this outcome has yet been replicated.…”
Section: Background and Rationalementioning
confidence: 99%